Memoirs of a teenage amnesiac - Zevin, Gabrielle (New York : Farrar Straus Giroux, 2007)
After a nasty fall, Naomi realizes that she has no memory of the last four years and finds herself reassessing every aspect of her life.
Keywords: Amnesia -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction